Does Quantity Generate Quality? Testing the Fundamental Principle of Brainstorming - Muñoz Adánez, Alfredo (The Spanish Journal of Psychology, 2005)
The purpose of this work is to test the chief principle of brainstorming, formulated as “quantity generates quality.” The study is included within a broad program whose goal is to detect the strong and weak points of creative techniques. In a sample of 69 groups, containing between 3 and 8 members, the concurrence of two commonly accepted criteria was established as a quality rule: originality and utility or value. The results fully support the quantity-quality relation (r = .893): the more ideas produced to solve a problem, the better quality of the ideas. The importance of this finding, which supports Osborn’s theory, is discussed, and the use of brainstorming is recommended to solve the many open problems faced by our society